Character as a Temporary Role (on the Material of Yu. Kim) (Proceedings of Southern Federal University. Philology, 2019)
Viktoria V. Arnautova (Ulyanovsk, Russian Federation)In the article it is considered the character as a figure being mostly distanced from life and a biographical author. The purpose of the paper is to analyse the peculiarities of the character poems in modern Russian Poetry on the example of Yuri Cherimovich Kim’s works. In the study it is used a narrative method as well as  comparison and  generalization. It is analyzed the role-based lyrics of Yu. Kim and concluded that  the person narrating in the character lyrics is nothing more than a role consciously played by the author in front of a reader /a listener /a spectator. It follows from the above that the author and the character distance themselves,  they are not identifiable. In Kim’s poems there is an extensive gallery of characters, each with its own individuality and a unique voice. Despite the diversity Yuliy Kim’s  characters are grouped into: intellectuals,  hard workers (a variation is prisoners), actors and clowns, students and schoolchildren,  fabulous and literary heroes. Free colloquial intonation, play and irony peculiar of Kim’s poetics emphasize the contrast between the author’s and the character’s consciousness. By entrusting his statement to the character, the author focuses on a certain pattern of behavior, demonstrates the features of someone else’s character and alien to him axiology.Key words: modern poetry, author, lyrical subject, character, Yu. Kim.DOI 10.23683/1995-0640-2019-4-154-159